Penerapan Sanksi Pidana Terhadap Penyalahgunaan Narkotika Dan Psikotropika Di Kalangan Remaja - Dwi Sri Rahmawati; Arjun Dwi Prasetya; Nabela Fitriani Utamawati; Taun Taun (Peneliti.net, 2023)
As stated in Law no. 35 of 2009, Narcotics are substances or drugs that can be derived from plants or non-plants, both synthetic and semi-synthetic, which can cause changes or decreased consciousness, loss of taste, eliminate or eliminate pain, and the possibility of dependence. Meanwhile, psychotropics as referred to in Law no. 5 of 1997, are substances or drugs that are not classified as narcotics, but still have a selective effect on the central nervous system which causes certain changes in mental activity and behavior. The purpose of qualitative research is to explore in depth a particular phenomenon by collecting data as complete as possible, emphasizing the importance of the depth and detail of the data studied. The purpose of this study is to examine the factors and consequences of enforcing criminal sanctions, as well as overcoming the problem of narcotics and psychotropic abuse. Qualitative methods were used in conducting this research. The development of qualitative methods has made it possible to study human life in certain causal scenarios, but executives argue that conceptual selection of symptoms is often neglected. The method used is in-depth or holistic, depending on the variability of the factors being studied. Causes of drug abuse can be categorized into two groups: internal factors, such as personality, anxiety, depression, and lack of religiosity; and external factors, such as the presence of certain substances, family circumstances, a weak legal system, and environmental influences. The use of criminal sanctions is intended to cause certain consequences for the perpetrator so that he does not repeat his actions. In addition, criminal sanctions serve as a means of reproach for the behavior of the offender. Various ways can be done to combat drug addiction, including preventive measures such as coaching and family supervision, curative measures such as medical treatment or other forms of therapy, rehabilitation programs to prevent relapse, and law enforcement as a means of repression.